The effect of Curing Process in Acetic Acid on the Gelatin Properties of Blingon Goat Skin - M. I. Said; S. Triatmojo; Y. Erwanto; A. Fudholi (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2014)
Bligon goat is a cross between Kacang with Ettawah goat. The skin of Bligon goat contains collagen protein compounds that have the potential to be processed into gelatin. Curing process is necessary to improve the properties of gelatin both quantitative and qualitative. The purpose of this study was to identification of the best process time and level of acetat acid as curing materials of Blingon goat skin. The skin of male Bligon goat age ±1.5-2.5 years of old and acetic acid (CH3COOH 0.5 M) were used as material. The experiment was run according to completely randomized design (CRD) with factorial pattern of 2x3 and three replications for each treatment. Two processing time (48 and 96 hours) as first factor and three concentrations levels of acetic acid (3, 6 and 9%, v/v) as the second factor. The data were analyzed by analysis of variance. Yields, gel strength and viscosity were used as parameters. The results of this study showed that the processing time up to 96 hours and level of concentration up to 9% significantly affected (P<0.01 ) gel strength, but no significantly on the yields and viscosity. The combination of processing time of 96 hours with concentration level of 3% gave the best results compared to others.